A prolonged intensive care unit stay defines a worse long-term prognosis: insights from the critically ill mortality by age (Cimba) study - Bento Rodrigues, Ana Rita (2024)
© 2024 Australian College of Critical Care Nurses Ltd. Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/ licenses/by/4.0/)